SUBTEXT AND IMPLICATIVE PARADIGM IN A LYRICAL TEXT (Scientific journal of the Fergana State University, 2026)
The article discusses implicative units that are part of the object of study of pragmalinguistics. Also, the use of subtext in the literary text is analyzed through linguistic evidence. Particular attention is paid to the study of implicit phenomena used in both poetic and prose texts.